Prisoners of Isolation Solitary Confinement in Canada - Jackson, Michael (Heritage, 2019)
What is it really like in 'the hole'? On what basis do prison officials employ the most drastic of carceral punishments – solitary confinement – and to what effect? Michael Jackson, lawyer, professor, activist, made a point of finding out. Approached in 1974 by a group of prisoners in the British Columbia Penitentiary, Jackson listened to their stories, investigated, and became convinced that these prisoners were being held in solitary confinement under unlawful conditions and for arbitrary and unjustified reasons. He then helped launch proceedings on their behalf to have the imposition of solitary confinement in the B.C. Penitentiary declared 'cruel and unusual punishment.' Jackson sets out the facts and legal arguments presented to the Federal Court of Canada against a background of the historical evolution of solitary confinement and penitentiary discipline. Successfully argued, the McCann case (1975) was unique in Canadian judicial history. Since then Jackson has remained in close touch with his prison contacts, maintaining a watching brief on whether prison practice has conformed to the rule of the law. He traces the continuation of solitary confinement in the newest of Canada's maximum security institutions and describes the conditions in the 'special handling units,' the most recent addition to Canada's 'carceral archipelago.' It is clear from his findings that prison officials continue to violate human rights. Though Jackson eschews sensationalism, the raw facts and the record of direct testimony he presents make Prisoners of Isolation a disturbing book